In vitro and in silico Evaluations of Chemical Constituents from the Rhizomes of Aglaonema simplex (Blume) Blume as Hyaluronidase Inhibitor - Khammee, Thongchai; Rujitanapanich, Sawittree; Chunhakant, Sutthiduean; Jaratrungtawee, Amornmart; Kuno, Mayuso (Thai Journal of Science and Technology, 2020)
From rhizomes extract of Wan Khan Mak [Aglaonema simplex (Blume) Blume] long-chain ester, butyl stearate (1) and a phytosterol, b-sitosterol (2) were isolated. The structures of two isolated compounds were elucidated by using analysis of their spectroscopic data, and compared with the reported value of the known compounds. The isolated compounds were further evaluated for in vitro hyaluronidase enzyme inhibition assay. Compound 2 (IC50 = 888.5±44.9 µg/mL) exhibited mild hyaluronidase inhibitory activity as compared with the standard 6-O-palmitoylascorbic acid (IC50 = 186.1±3.9 µg/mL). Moreover, a molecular docking study of the highest hyaluronidase inhibitor was carried out to understand the binding mode of the inhibitors into the binding site of hyaluronidase.